Aphis craccivora Koch, 1854 (Hemiptera: Aphididae) infesting mahogany seedlings (Swietenia macrophylla King, Meliaceae) and scarlet jade vines (Mucuna bennettii F. Muell., Fabaceae) - Marcelo T. Castro; Sandro C. L. Montalvão; Suzan B. Z. Cunha; Rose G. Monnerat (Entomological Communications, 2020)
Aphis craccivora Koch, 1854 (Hemiptera: Aphididae) is a highly polyphagous aphid that is considered a pest of many crops with economic interest. The present study reports the occurrence and plant damages caused by the aphid A. craccivora on mahogany seedlings (Swietenia macrophylla King, Meliaceae) and scarlet jade vines (Mucuna bennettii F. Muell., Fabaceae) in the Distrito Federal, Brazil. Infestations of this aphid were found in twelve mahogany seedlings and two scarlet jade vines. The infestations caused deformations in the young leaflets of mahogany plants as well as leaves and inflorescences of scarlet jade vine. A. craccivora negatively affected the development of S. macrophylla and might become a limiting factor for seedlings production.